STATUS REPRODUKSI DAN ESTIMASI OUTPUT BERBAGAI BANGSA SAPI DI DESA SRIWEDARI, KECAMATAN TEGINENENG, KABUPATEN PESAWARAN - Septia Anggraini; Sulastri ,; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The aim of this research is to know the status of reproduction, NI, NRR, and output of some cattle breeds at Sriwedari Village, Tegineneng Districts, Pesawaran Regency.  The research was carried out for two months, started in Agustus until September 2015. The data was taken from all of the cattle farmers in Sriwedari Village. The result shows that the structure of cattle population in Sriwedari Village are consisted of 123 animal unit (AU) PO cattle, 57,50 AU Limousin Crossbreed, 173,50 AU Simmental Crossbreed, 9 AU Brangus Crossbreed. Female cattles were breed by artificial insemination, the first mating age of PO cattle was 17,25 months, Limousin Crossbreed was 18,85 months, Simmental Crossbreed was 17,77 months, and Brangus Crossbreed 15,5 months.  S/C Brangus Crossbreed was 2, PO cattle was 2,07, Limousin Crossbreed was 2,14, and Simmental Crossbreed 2,16.  Calving interval of  PO cattle was 14,13 months, Simmental Crossbreed was 13,94 months, Brangus Crossbreed was 13,85 months, and Limousin Crossbreed was 13,74 months.  The length of breeding of PO cattle was 7,83 years, Limousin Crossbreed was 6,74 years, Simmental Crossbreed was 6,29 years, and Brangus Crossbreed  was 6,63 years.  Natural increase of Simmental Crossbreed  was 42,62%, PO cattle was 17,99%, Limousin Crossbreed  was 9,84%, Brangus Crossbreed was 9,09%.  Net replacement rate of PO cattle 333,668%, Limousin Crossbreed was 281,818%, Simmental Crossbreed  was 261,588%, Brangus Crossbreed  was 228,571%.  Output of  Simmental Crossbreed was 27,07%, PO cattle was 20,86%, Limousin Crossbreed was 14,75%, Brangus Crossbreed was 9,09%. (Keywords: reproduction, population, output, cattle, breeds)